2017
DOI: 10.1002/mp.12471
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Evaluation of plastic scintillator detector for small field stereotactic patient‐specific quality assurance

Abstract: Among all three detectors, PSD demonstrated superior performances in plans with small fields and heavy modulation. High consistency and low uncertainty made PSD a suitable detector for clinical routine SRS QA. PinPoint chamber should be avoided for targets smaller than 0.2 cc; film dosimetry can be utilized with careful evaluation of its uncertainty bracket. Compared to PSD measurements, AcurosXB calculation demonstrated high accuracy for nonmodulated small fields. The positive correlation between plan modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…PSD have been shown to produce less perturbations in the charged particle fluence and are therefore appropriate detectors for small field measurements. 8,9 Moreover, the small active volume (0.002 cc) of the PSD avoids volume averaging effects and the measured output values agreed well (within 3%) with the dose calculated from Monte Carlo (MC) simulations. [10][11][12] In contrast to diode detectors, PSD are energy independent and hence no daisy chain method was necessary.…”
Section: A Commissioning Mobiussupporting
confidence: 59%
“…PSD have been shown to produce less perturbations in the charged particle fluence and are therefore appropriate detectors for small field measurements. 8,9 Moreover, the small active volume (0.002 cc) of the PSD avoids volume averaging effects and the measured output values agreed well (within 3%) with the dose calculated from Monte Carlo (MC) simulations. [10][11][12] In contrast to diode detectors, PSD are energy independent and hence no daisy chain method was necessary.…”
Section: A Commissioning Mobiussupporting
confidence: 59%
“…The W1 is similar to the W2 but is 3 mm long. Qin et al found that the W1 agreed with RCF to within 3%, with an average difference of 0.31 ± 1.20% …”
Section: Discussionmentioning
confidence: 94%
“…Miniature plastic scintillators have been developed that are nearly water equivalent . A commercial version of the detector described by Beddar et al, having dimensions 1 mm diameter and 3 mm long, has been investigated for measurements of depth dose and profiles of small fields, determination of field size correction factors for other detector types, small‐field dose measurements in heterogeneous media, and for patient‐specific QA of small‐field SRS plans . Recently, a second generation has been developed that is smaller, 1 mm instead of 3 mm length.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Several studies have reported the dosimetric characteristics of scintillation detectors and their use as dosimeters for quality assurance (QA) in proton therapy. [21][22][23][24][25][26][27][28][29][30] These studies showed that scintillator-based dosimetry systems offered a fast response and could be used as high-resolution dosimeter tools if the quenching effects were corrected. A commercially available scintillator-based dosimeter tool, Lynx (IBA Dosimetry, Louvain-la-Neuve, Belgium), has been used in proton beam measurements.…”
Section: Introductionmentioning
confidence: 96%
“…Several studies have reported the dosimetric characteristics of scintillation detectors and their use as dosimeters for quality assurance (QA) in proton therapy . These studies showed that scintillator‐based dosimetry systems offered a fast response and could be used as high‐resolution dosimeter tools if the quenching effects were corrected.…”
Section: Introductionmentioning
confidence: 99%